CRITERIA FOR EVALUATING QUALITY OF FOREIGN LANQUAGE TESTS - Яременко, Ірина; Токар, Лариса (SWorldJournal, 2022)
Different models of linguistic competences are analyzed. Certain principles of the development of the 1960s-1970s language tests are considered with the emphasis on their key problems and disadvantages. Test models, based on the principles of communicati